Bi-Univalent Function Classes Defined by Using a Second Einstein Function - Alaa H. El-Qadeem; Saleh A. Saleh; Mohamed A. Mamon (Journal of Function Spaces)
Motivated by q-calculus, subordination principle, and the second Einstein function, we define two families of bi-univalent analytic functions on the open unit disc of the complex plane. We deduce estimates for the first two Maclaurin’s coefficients and the Fekete-Sezgö functional inequalities for the functions that belong to these families of functions.